2023
DOI: 10.3389/fmicb.2023.1124917
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary crude protein levels in the concentrate supplement after grazing on rumen microbiota and metabolites by using metagenomics and metabolomics in Jersey-yak

Abstract: IntroductionThe crude protein level in the diet will affect the fermentation parameters, microflora, and metabolites in the rumen of ruminants. It is of great significance to study the effect of crude protein levels in supplementary diet on microbial community and metabolites for improving animal growth performance. At present, the effects of crude protein level in supplementary diet on rumen fermentation parameters, microbial community, and metabolites of Jersey-Yak (JY) are still unclear.MethodsThe purpose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 71 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…In this experiment, 18 healthy, 6-monthold male Jersey-yaks (bred through artificial insemination of yaks with frozen semen of the same batch of Jersey cattle) were selected. A total of 18 Jersey-yaks were randomly assigned to three experimental groups based on their initial body weights using R software (v.4.1.2) [4]. The treatments of the three groups were as follows: (1) no supplementary feeding (as a control group, low protein level, LP); (2) supplementary low-protein diet (crude protein content: 15.16%; medium protein level, MP); (3) supplementary high-protein diet (crude protein content: 17.90%; high protein level, HP).…”
Section: Experimental Animals and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…In this experiment, 18 healthy, 6-monthold male Jersey-yaks (bred through artificial insemination of yaks with frozen semen of the same batch of Jersey cattle) were selected. A total of 18 Jersey-yaks were randomly assigned to three experimental groups based on their initial body weights using R software (v.4.1.2) [4]. The treatments of the three groups were as follows: (1) no supplementary feeding (as a control group, low protein level, LP); (2) supplementary low-protein diet (crude protein content: 15.16%; medium protein level, MP); (3) supplementary high-protein diet (crude protein content: 17.90%; high protein level, HP).…”
Section: Experimental Animals and Managementmentioning
confidence: 99%
“…Because yaks live in high-altitude areas of 2000-5000 m, extremely harsh natural environmental conditions such as low temperature and low oxygen lead to a slow growth [3]. People use frozen semen of high-quality cattle such as Jersey cattle and Angus cattle to hybridize yaks through artificial insemination technology to achieve the purpose of improving the production performance of yaks [4]. Jersey-yak is a hybrid offspring of Jersey cattle and yak (a hybrid offspring of female yaks artificially inseminated with high-quality frozen semen of Jersey cattle).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, an increasing number of researchers have adopted a combined multi-omics analysis approach to reveal the effect of ingested dietary nutrients on animal growth performance and rumen microbes ( Xue et al, 2020 ). In one study, macrogenomics and metabolomics were used to analyze rumen microbiota in yak and it was found that dietary crude protein levels affect metabolites associated with bile secretion and histidine metabolism in the rumen, and these compounds were associated with rumen dominant microbiota ( Dai et al, 2023 ). Similarly, a multi-omics analysis of rumen fluid from Holstein heifers revealed a reduction in the relative abundance of cellulose-degrading bacteria in the rumen with higher dietary concentration.…”
Section: Introductionmentioning
confidence: 99%